Why They Choosing Career To Be A Seaman? - Popo Hartoyo (Diponegoro University, 2022)
This study aims to explain the factors underlying the cadets in determining seaman as the chosen profession / career. The independent variables in this study were Extrinsic Motivation, Intrinsic Motivation, Labor Market Motivation, Career Motivation, and Cadets / Student Perceptions. The dependent variable is career interest as a seaman. Object of research at Djadajat Maritime Academy Jakarta. The author has used the survey method in this paper. The author collects data from 240 cadets who have studied for at least 1 year at the Djadajat Maritime Academy and have not carried out 1-year sea service practices onboard vessel as regulated. The results showed that what influenced their interests as sailors was due to intrinsic motivation and perception. To the author's knowledge, this is the first study that shows students' motivation when deciding to become seaman. For the organizations, this study can be the basis for determine the right learning method to improve seaman competency